2006
DOI: 10.1590/s0482-50042006000600006
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia associada ao envelhecimento: aspectos etiológicos e opções terapêuticas

Abstract: artigo dE rEvisão rEviEw articlE RESUMO A prevalência de incapacidade e dependência funcional é maior em idosos e está intimamente associada à redução da massa muscular, que ocorre, até mesmo, em indivíduos saudáveis. A sarcopenia parece decorrer da interação complexa de distúrbios da inervação, diminuição de hormônios, aumento de mediadores inflamatórios e alterações da ingestão protéico-calórica que ocorrem durante o envelhecimento. A perda de massa e força muscular é responsável pela redução de mobilidade e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
99

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(177 citation statements)
references
References 55 publications
0
43
0
99
Order By: Relevance
“…Sarcopenia, defined as the slow, progressive and apparently inevitable loss of muscle mass and strength, is one of the most important physiological changes that occur with advancing age 1 . The reduction of muscle mass associated with aging seems to be the primary factor responsible for reduction in muscle strength and power and the consequent loss of functional mobility in elderly people [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…Sarcopenia, defined as the slow, progressive and apparently inevitable loss of muscle mass and strength, is one of the most important physiological changes that occur with advancing age 1 . The reduction of muscle mass associated with aging seems to be the primary factor responsible for reduction in muscle strength and power and the consequent loss of functional mobility in elderly people [2][3][4] .…”
Section: Introductionmentioning
confidence: 99%
“…According to Silva et al (2006) and Roberts (1995) malnutrition is a serious factor for sarcopenia since the majority of the elderly do not consume enough protein according to the recommended daily intake of protein. Houston et al (2008) evaluated a group of elderly in order to associate protein diet and muscle mass loss and concluded that a diet with proteins can be a modifiable risk factor to reduce the risk of sarcopenia.…”
Section: Resultsmentioning
confidence: 99%
“…Matz (1968 apud SILVA;SILVA;CHANG, 1998), argues that the biscuits with very high or very low expansion index cause problems to the industry resulting in very high weight or small-sized products.…”
Section: Sensory Evaluation Performed By the Target Groupmentioning
confidence: 99%
“…Consequences include falls, dependency, disability, decreased QoL, institutionalization and death. 8,9 It is a process with a singular and complex biological basis, which cannot be explained only by senescence.…”
Section: Introductionmentioning
confidence: 99%